Ответы 2

  • 1,2:х=1,7-2,11,2:х=-0,4х=1,2:(-0,4)х=-3(2+х):0,4+6,5=1,5 так?(2+х):0,4=1,5-6,5(2+х):0,4=-55+х:0,4=-5х:0,4=-5-5х:0,4=-10х=-10*0,4х=-4
  • ▪1,2:х+2,1=1,71,2:х=1,7-2,11,2÷х= -0,4х=1,2÷(-0,4)х= -3-------Проверка:1,2:(-3)+2,1= -0,4+2,1=1,7▪(2+х):0,4+6,5=1,5(2+х):0,4=1,5-6,5(2+х):0,4= -52+х= -5×0,42+х= -2х= -2-2х= -4----------Проверка:(2+(-4)):0,4+6,5= -2÷0,4+6,5= -5+6,5=1,5
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years